2010
DOI: 10.1007/s00421-010-1592-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis by two-dimensional Blue Native/SDS-PAGE of membrane protein alterations in rat soleus muscle after hindlimb unloading

Abstract: Muscle atrophy occurring in several pathophysiological conditions determines decreases in muscle protein synthesis, increases in the rate of proteolysis and changes in muscle fiber composition. To determine the effect of muscle atrophy induced by hindlimb unloading (HU) on membrane proteins from rat soleus, a proteomic approach based on two-dimensional Blue Native/SDS-PAGE was performed. Proteomic analysis of normal and HU soleus muscle demonstrates statistically significant changes in the relative level of 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…With this method we are able to detect proteins with molecular masses between 10 kDa and up to 200 kDa. 2D BN/SDS-PAGE on skeletal muscle proteins was performed as previously described [6] with some modifications. Briefly, 250 µg of protein sample was applied on 4–15% polyacrylamide native gradient gels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this method we are able to detect proteins with molecular masses between 10 kDa and up to 200 kDa. 2D BN/SDS-PAGE on skeletal muscle proteins was performed as previously described [6] with some modifications. Briefly, 250 µg of protein sample was applied on 4–15% polyacrylamide native gradient gels.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work we hypothesized that AQP4, together with the endothelial AQP1, allows high water exchange between the blood and the fibers in order to regulate volume changes occurring during muscle activity [2] which may be related to the substantial muscle swelling and intracellular osmolyte production occurring during exercise [3][5]. The physiological relevance of this water channel in the skeletal muscle is supported by the fact that muscle activity modulates AQP4 expression as it is evident during disuse [6], [7].…”
Section: Introductionmentioning
confidence: 98%
“…It is associated with multiple types of skeletal muscle change and atrophy, 11 dysregulated gene expression that leads to altered protein synthesis and hemodynamics, 12 oxidative stress, 13 altered metabolism, 14 increased fatigability, 15 and vestibular issues. 16 In addition, aquaporin-4 (AQP4), a water channel protein involved in regulating water balance in the brain, 17,18 has been shown to be altered following hindlimb unloading, 19,20 a well-established Earth-bound model of microgravity that involves suspending a rodents’ hindlimbs off the ground for an extended period of time (see Materials and Methods for details). It has been suggested 19 that the increase in AQP4, which is prevalent in the neuromuscular system, 21 is a response to compensatory mechanisms initiated by muscle atrophy from extended periods of unloading.…”
Section: Introductionmentioning
confidence: 99%
“…In general, muscular atrophy is associated with a drastic decrease in protein synthesis and concomitant increase in the rates of protein breakdown, as well as slow-to-fast transitions in contractile kinetics and an oxidative-to-glycolytic shift in fiber metabolism [195]. A considerable number of gel-based studies have used animal models of denervation, immobilization or extended periods of muscle disuse to determine proteome-wide changes during muscular atrophy [196,197,198,199,200,201,202,203,204,205]. These studies have confirmed the general tendency of atrophying skeletal muscles to undergo a stepwise conversion to faster contractile properties and increased glycolytic metabolism.…”
Section: Comparative Skeletal Muscle Proteomics Using Two-dimensiomentioning
confidence: 99%
“…The proteomic profiling of rat muscles following denervation [196], hindlimb suspension [197] or immobilization by the pin-heel method [198] showed increases in carbonic anhydrase CA3, enolase and fast MLC, as well as decreases in the fatty acid binding protein and slow MLC. As described in the proteomic studies listed in Table 2, neuromuscular unloading is clearly associated with a slow-to-fast transformation process [199,200,201,202,203] and complete denervation triggers extensive isoform switching in slow versus fast isoforms of the contractile proteins MyHC, MLC, TN and TM [204,205]. As already mentioned in above section on exercise proteomics, vibration training can be beneficial to counteract muscular atrophy triggered by extended periods of bed rest [174,175].…”
Section: Comparative Skeletal Muscle Proteomics Using Two-dimensiomentioning
confidence: 99%